The Influence of Experiential Marketing on Customer Satisfaction and Loyalty of Corner Coffee Shop in Langsa - Arismunandar, T Maureza; Hartoyo, Hartoyo; Krisnatuti, Diah (Jurnal Manajemen dan Agribisnis, 2019)
The level of coffee consumption is on a raging level, making the coffee shop business is also increasingly emerging in the form of both local coffee shops and international coffee shops. Coffee Corner is the first coffee shop in Langsa city that combines traditional and modern aspects in its presentation. To ensure business continuity, Kedai Coffee Corner has to create a strategy so that it can boost their customer satisfaction and loyalty by providing experience that can be formed through five dimensions of sense, feel, think, act and relate. This study aims to analyze the influence of experiential marketing on customer satisfaction and loyalty. Corner coffee shop customers of which criteria is above than 17 years old and willing to be respondents are taken and as many as 180 respondents are selected using accidental sampling technique, then the respondents fill out a questionnaire that contains a statement about the variables studied so that the data obtained will then be processed using Structural Equation Modeling (SEM). The result of the research shows that experiential marketing has a significant effect on customer satisfaction and loyalty either directly or indirectly. Experiential marketing is reflected by two dimensions that have the greatest contribution and those are sense and relate. Better quality and aroma of the coffee, as well as superiority in fragrant than other coffee shops, is the indicator that contributes the most to the sensory dimension. An excellent coffee image and quality of the presentation are the indicators that contribute the most to the relative dimension.